2021
DOI: 10.4103/atm.atm_683_20
|View full text |Cite
|
Sign up to set email alerts
|

Bilevel positive airway pressure ventilation for non-COPD acute hypercapnic respiratory failure patients: A systematic review and meta-analysis

Abstract: The effectiveness of bi-level positive airway pressure (BiPAP) in patients with acute hypercapnic respiratory failure (AHRF) due to etiologies other than chronic obstructive pulmonary disease (COPD) is unclear. To systematically review the evidence regarding the effectiveness of BiPAP in non-COPD patients with AHRF. The Cochrane Library, MEDLINE, EMBASE, and CINAHL Plus were searched according to prespecified criteria (PROSPERO-CRD42018089875). Randomized controlled trials (RCTs) assessing the effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Hypercapnia secondary to COPD is well represented within the included literature, featuring in all ( n = 7) of the included studies. Faqihi et al 43 note the scarcity of literature regarding NIV intervention in AHRF outside of COPD and cardiogenic pulmonary oedema, particularly in relation to common conditions such as obesity hypoventilation syndrome. Golmohamad et al 44 also make recommendations against the use of HFNC in the management of patients with obesity hypoventilation syndrome/sleep disordered breathing, owing to the lack of research in the area and the incidence of treatment failure in this patient subgroup within their observational study.…”
Section: Discussionmentioning
confidence: 99%
“…Hypercapnia secondary to COPD is well represented within the included literature, featuring in all ( n = 7) of the included studies. Faqihi et al 43 note the scarcity of literature regarding NIV intervention in AHRF outside of COPD and cardiogenic pulmonary oedema, particularly in relation to common conditions such as obesity hypoventilation syndrome. Golmohamad et al 44 also make recommendations against the use of HFNC in the management of patients with obesity hypoventilation syndrome/sleep disordered breathing, owing to the lack of research in the area and the incidence of treatment failure in this patient subgroup within their observational study.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Corresponding clinical results indicated that the hypoxemia of patients with pulmonary edema and acute MI was evidently alleviated through BiPAP treatment; further, the success rate of rescuing left HF was significantly improved. 6…”
Section: Introductionmentioning
confidence: 99%
“…3,5 Corresponding clinical results indicated that the hypoxemia of patients with pulmonary edema and acute MI was evidently alleviated through BiPAP treatment; further, the success rate of rescuing left HF was significantly improved. 6 Cardiac hypertrophy and fibrosis can serve as adaptive, compensatory, or maladaptive precursors of cardiac failure. Accumulating evidence has confirmed that ROS signaling is associated with the initiation of cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In patients with hypercapnia without COPD, NIV reduces the need for intubation compared to standard oxygen therapy, with similar efficacy between BPAP and CPAP. 6 The evidence supporting the use of NIV…”
mentioning
confidence: 99%